2003
DOI: 10.2460/ajvr.2003.64.310
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary protein quality and essential fatty acids on fatty acid composition in the liver and adipose tissue after rapid weight loss in overweight cats

Abstract: These data provide direct evidence that dietary protein quality alters fatty acid composition of tissues during weight loss in cats. The fatty acid patterns observed suggest that protein quality may alter fatty acid composition through modulation of desaturase activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
5

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 18 publications
(19 reference statements)
0
9
0
5
Order By: Relevance
“…Also, in another study 32 conducted by our laboratory group, we found that cats fed a complete, balanced, energy-dense diet that contained sufficient amounts of n-3 LPUFAs during weight gain had minimal lipid accumulation in the liver, and the concentration of 22:6(n-3) in storage and membranes was substantially increased over baseline values. In the overweight cats, there was a significant decrease in n-6 and n-3 LPUFAs in liver TGs, compared with values for lean cats at baseline.…”
Section: Discussionmentioning
confidence: 75%
“…Also, in another study 32 conducted by our laboratory group, we found that cats fed a complete, balanced, energy-dense diet that contained sufficient amounts of n-3 LPUFAs during weight gain had minimal lipid accumulation in the liver, and the concentration of 22:6(n-3) in storage and membranes was substantially increased over baseline values. In the overweight cats, there was a significant decrease in n-6 and n-3 LPUFAs in liver TGs, compared with values for lean cats at baseline.…”
Section: Discussionmentioning
confidence: 75%
“…Nevertheless, a large intake of carbohydrates may contribute to sustain low plasma levels of homocysteine [19]. Also, the finding of a positive correlation between protein intake and plasma arachidonic acid could indicate a greater production of eicosanoids, proinflammatory products that may facilitate the development of insulin resistance, a conclusion also suggested by the close, albeit not significant, correlation between protein intake and both insulinemia and HOMA index [20,21,22].…”
Section: Discussionmentioning
confidence: 84%
“…Muitos são os trabalhos na literatura que estudam os efeitos dos esteróides sexuais sobre o metabolismo corpóreo [1][2][3][4][5][6][7][8][9] . Dentre os modelos experimentais, os ratos albinos são os mais utilizados por apresentarem um ciclo estral bastante conhecido e de curta duração (média de 4-5 dias) e atingirem rapidamente o amadurecimento sexual aos 50-60 dias de vida.…”
Section: Discussionunclassified
“…A relação entre hormônios femininos e variação ponderal em modelo experimental também vem sendo pesquisada. Vários autores descreveram ganho ponderal em animais ooforectomizados 3,4,8 . Com o advento da terapia de reposição hormonal e a descoberta da leptina, um hormônio regulador da obesidade, a discussão sobre obesidade e supressão estrogênica vem sendo mais freqüente 9 .…”
Section: Introductionunclassified